Employment of Waste for Irrigation Purposes - Kumar, Dinesh; Jha, Kumod Ranjan; Gaur, Kanishk; Kumar, Gaurav; Bhardwaj, Ojasvi (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
This paper deals with Irrigation using treated agricultural or food processing industry as wastewater can allow more intensive use of the land, improve plant vigour and may extend growing seasons. Nutrients in wastewater (as organic carbon, nitrogen, phosphorus and potassium) can be balanced to plant growth needs, or natural waters can have had nutrients added. This form of irrigation is called fertigation. Irrigation with chemical addition to vegetation needs an effective environmental management plan (EMP) to prevent harm to the environment. Our aim in this paper is to give ways that ensure that resources are used efficiently, that land is not degraded or waterlogged and that natural waters are protected from salinity, turbidity, nutrient-enrichment, leached trace metals, pesticides and other harmful wastewater contaminants.